MATURAÇÃO E DORMÊNCIA DE SEMENTES DE GRAMA BATATAIS - Toledo, Francisco Ferraz de; Marcos Filho, Júlio; Silvarolla, Maria Bernardete; Batista Neto, José Ferreira (REVISTA DE AGRICULTURA, 2015)
MATURAÇÃO E DORMÊNCIA DE SEMENTES DE GRAMA BATATAIS